The COVID-19 pandemic: A threat to higher education? Evidence from a large university in Northern Italy - Marina Bonaccolto-Töpfer; Carolina Castagnetti (Journal for Labour Market Research, 2024)
Transition to online teaching during the first wave of the COVID-19 pandemic has led to various concerns about educational quality. The study investigates the consequences of this transition on student performance for a prominent university in Northern Italy. Comprehensive administrative data allows us to monitor students' performance and to have detailed socioeconomic information about them. Using a difference-in-differences design with lecturer fixed effects, we exploit the unique timing of the lockdown that fell together with the start of the summer term in 2020. We find no marked effects on students' average grades in higher education in the immediate aftermath of the lockdown.
Keywords: I18; I23; G18; I24; 330; Higher education; COVID-19 pandemic; Difference-in-differences; Online teaching